11th AIAA/CEAS Aeroacoustics Conference 2005
DOI: 10.2514/6.2005-2995
|View full text |Cite
|
Sign up to set email alerts
|

Permeable Surface Corrections for Ffowcs Williams and Hawkings Integrals

Abstract: The acoustic prediction methodology discussed herein applies an acoustic analogy to calculate the sound generated by sources in an aerodynamic simulation. Sound is propagated from the computed flow field by integrating the Ffowcs Williams and Hawkings equation on a suitable control surface. Previous research suggests that, for some applications, the integration surface must be placed away from the solid surface to incorporate source contributions from within the flow volume. As such, the fluid mechanisms in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 24 publications
1
37
0
Order By: Relevance
“…There are only minor differences between the solutions for the permeable and solid surfaces, most likely caused by vortices crossing the downstream portions of the porous surfaces. 21,22 At this low frequency with a Helmholtz number kD = 0.19, it is very unlikely that there are any flow effects on the radiated noise. Therefore, only results for the solid surfaces will be presented in the remainder of the paper.…”
Section: Ivd Acoustic Radiationmentioning
confidence: 99%
“…There are only minor differences between the solutions for the permeable and solid surfaces, most likely caused by vortices crossing the downstream portions of the porous surfaces. 21,22 At this low frequency with a Helmholtz number kD = 0.19, it is very unlikely that there are any flow effects on the radiated noise. Therefore, only results for the solid surfaces will be presented in the remainder of the paper.…”
Section: Ivd Acoustic Radiationmentioning
confidence: 99%
“…The surfaces were extracted from the CFD multi-block structured grid used for the CFD. A first set of rigid surfaces includes the wall surfaces on the wing leading edge (1-7) and on the slat pressure side (8)(9)(10)(11). Then, three sets of porous surfaces are available near the external boundary of the computational domain.…”
Section: American Institute Of Aeronautics and Astronauticsmentioning
confidence: 99%
“…It has been shown that escaping eddies through an integration surface can generate spurious noise. 7,8 This issue makes it difficult to attribute additional noise contributions, as compared to solid surface predictions, to quadrupole sources or spurious noise generated numerically. Since it is still computationally infeasible to resolve and propagate the effect of all relevant quadrupole sources in a realistic engineering problem, we turn to a model problem that captures the salient physics but at a cost that allows the opportunity to address the questions at hand.…”
Section: Introductionmentioning
confidence: 98%